2001
DOI: 10.1046/j.1464-4096.2001.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde ureteropyeloscopic holmium laser lithotripsy for large renal calculi

Abstract: Objective To assess the ef®cacy and safety of the retrograde ureteropyeloscopic holmium laser for treating renal stones that are too large to treat with extracorporeal shock wave lithotripsy (ESWL). Patients and methods Thirty patients (22 men and eight women, mean age 43 years, range 18±62) with a renal stone burden of >2 cm were selected for laser treatment. The stones were in the renal pelvis in 16 patients, lower calyx in ®ve, middle calyx in two, upper calyx in one and multiple pelvic and calyceal in six.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
3
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 20 publications
5
55
3
1
Order By: Relevance
“…[2] Although this procedure has a high stone-free rate, it has significant complications despite technological advancements. [5][6][7] The low success rate of ESWL and the high morbidity of PCNL in lower calyx stones directed investigators to other alternatives. RIRS is a reasonable alternative to PCNL and ESWL in lowvolume lower calyx stones, because it has a lower complication rate compared with PCNL and a stone-free rate similar to that of ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Although this procedure has a high stone-free rate, it has significant complications despite technological advancements. [5][6][7] The low success rate of ESWL and the high morbidity of PCNL in lower calyx stones directed investigators to other alternatives. RIRS is a reasonable alternative to PCNL and ESWL in lowvolume lower calyx stones, because it has a lower complication rate compared with PCNL and a stone-free rate similar to that of ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…Several single-institution case series of RIRS for large renal stones have been reported [28,29,30,31,32,33,34,35,36]. In 1998, Grasso et al [28] first reported 48 patients with upper urinary tract and minor staghorn calculi >2 cm who underwent RIRS, with an 81% (34 of 45 renal and 20 of 21 ureteral) stone-free rate in a single procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Second-stage procedures were carried out in 18 patients (8 of 15 large renal and 1 of 3 complex ureteral stone burdens), and the success rate increased to 94% without intraoperative complications. The study by El-Anany et al [29] showed that stone fragmentation was achieved in only 23 (77%) patients because of poor visualization. In recent years, more and more doctors have been able to skillfully operate the flexible ureteroscope and determine the efficacy of ureteroscopy as an alternative to PCNL to tackle large renal stones.…”
Section: Discussionmentioning
confidence: 99%
“…Technological improvements in the new generation of ureteroscopes such as small caliber URSs and digital optics and advances in laser lithotripsy have made the use of RIRS for renal stones more popular [4,5]. It has been widely accepted that RIRS procedures significantly decreased morbidity rates in the management of renal stones [17,18]. RIRS has good efficacy and less morbidity in the treatment of large renal stones.…”
Section: Discussionmentioning
confidence: 99%